ChemInform Abstract: A Practical Procedure of Propargylation of Aldehydes. Issue 2 (9th January 2013) - Ghosh, Papiya; Chattopadhyay, Angshuman
Abstract Low‐valent iron‐ or tin‐mediated reactions of excess propargyl bromide with aldehydes afford homopropargyl alcohols as main or sole products.